INOVASI BATIK BERBASIS COLOR CHANGING-SUN ACTIVATED SEBAGAI UPAYA MELESTARIKAN WARISAN BUDAYA BATIK JAMBI MOTIF SUNGAI PENUH PADA KOMUNITAS BATIK SUNGAI PENUH - Mia Aina; Diah Riski Gusti; Damris Muhammad; Intan Lestari; Martina Asti Rahayu (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
As a resource, the local cultural value of Batik Jambi with the Sungai Penuh motif is one of the driving forces in the improvement of the economy, capacity, expertise, and reputation of the region. In reality, the development of Batik Jambi with the Sungai Penuh motif is still relatively stagnant. The demand and interest in Batik Jambi with the Sungai Penuh motif have not seen significant growth from year to year. It is can be attributed to several issues, one of which is the lack of knowledge and skills regarding innovation in batik making, resulting in no distinguishing features compared to other batik motifs from the archipelago. As a solution to this problem, training and mentoring should be provided to members of the Batik community in Sungai Penuh City to innovate the Batik products they produce. The innovation introduced in this program involves the use of photochromic dyes. The basis of photochromic dyeing is the phenomenon of reversible color change induced by light in photochromic molecules, causing the molecules to exist in two different forms. These two different forms of molecules result in different colors. Practically observed, photochromic dyeing causes the applied batik products to change color when exposed to sunlight (color-changing - sun activated).